Influence of moon phases and stake posistion in the Branch on the development of manioc seedlings in the field (Research, Society and Development, 2023)
In the course of time, various peoples were led by empirical knowledge to the conduct of nature, driven, among other reasons, by beliefs and mysteries not yet completely revealed by modern science, such as the influence of the lunar phases during the life cycle of plants. The objective of this work was to evaluate the interactions that occur between the phases of the Moon and the position of the stem in the branch in the development of seedlings of cassava. The research was conducted in the Experimental Area of the Nucleus of Aromatic and Medicinal Plants - NUPLAM, Cento of Agricultural Sciences - CCA of the Federal University of Piauí - UFPI, in the period between September and November of 2017. The design used was randomized blocks (DBC) with dose treatments, arranged in a 4x3 factorial arrangement and three replicates. The treatments were composed by the phases of the Moon: New Moon (LN); Crescent Moon (LC); Full moon (LCO) and waning moon (LM) and three positions of the cuttings in the branch: stake pointer (EP); staking (EM) and basal cutting (EB). The parameters evaluated were: fresh shoot weight (PFFA) and root (PFFR) weight and dry shoot weight (PFSA) and root weight (PFSR). The best results were provided by the phases of the waning and full moon and the positions of the stakes in the branch, basal and median.